A study of the degree of genetic variation among populations of cacao grown in Nicaragua - Erielda Corrales; Regina Lacayo; Herman Mariano (African Journal of Environmental Economics and Management, 2014)
The use of local germplasm of THEOBROMA CACAO L. as a basis for developing a breeding program is limited by the lack of information on genetic variability and relationships among populations. This study covered a sample of 70 cocoa trees in five geographical areas of Nicaragua: El Rama, Nueva Guinea, Muelle de los Bueyes, El Castillo and Los Guatusos. The samples were molecularly analyzed using 10 microsatellite (SSR) DNA. For the 10 locus was achieved amplification of 95 alleles. Populations showed an average observed heterozygosity (Ho) of 0.522, and Nueva Guinea was the population with the value of Ho closest in value of expected heterozygosity (He). The latter obtained the lowest inbreeding rate (ƒ = 0.06). The value obtained for the average Fixation Index FST was 0.23, which allows you to catalog the cocoa plantations of southeastern of Nicaragua with a moderate level of genetic diversity. The populations of Muelle de los Bueyes and El Castillo presented the maximum value of genetic distance (0.1784). According to the Principal Coordinate Analysis, the population distribution in a geometric plane can be grouped into two blocks. Finally, the study phylogenetic populations of Castillo and Guatusos are more closely related to each other, than the rest of the population.